HLA-B*58:01 genotyping prevalence and the association with allopurinol-induced severe cutaneous adverse reactions: a living systematic review and meta-analysis - Hong Tham Pham; Manh Hung Tran; Thuy-Van Mai Hoang; Ai-Hoc Nguyen; Minh-Hoang Tran (Scientific Reports)
Abstract Evidence on the prevalence of HLA-B*58:01 genotyping and its association with allopurinol-induced severe cutaneous adverse reactions (SCARs) is lacking, especially in low-resource settings. We addressed these gaps by conducting comprehensive and race/ethnic origin-specific evaluations. We conducted a systematic search from inception to 31 December 2022 using databases (PubMed, Embase, and medRxiv), Google (for Vietnamese articles), and manual searching. We included original studies that investigated the association between HLA-B*58:01 genotyping and allopurinol-induced SCARs. We excluded studies on: (1) animals; (2) pharmacokinetics/pharmacodynamics; (3) genetic markers or genetic testing methods; (4) single group; and (5) cost-effectiveness of screening. Risk of bias was assessed using Newcastle–Ottawa Scale. We used random-effects model to report the summary estimates and 95% confidence interval (95% CI) in the meta-analysis. We included 13,719 patients from 24 case–control studies. The prevalences of HLA-B*58:01 genotyping (overall 5.8%; 95% CI 2.9% to 11.5%; I2 = 98%) varied by races (Asian [7.7%; 95% CI 3.4% to 16.8%; I2 = 98%] and White in Eastern/Western Europe [2.3%; 95% CI 1.2% to 4.3%; I2 = 86%]) and ethnic origins (East and Central Asia [5.5%; 95% CI 1.5% to 17.8%; I2 = 98%] and South and Southeast Asia [12.9%; 95% CI 9.5% to 17.3%; I2 = 79%]). HLA-B*58:01 genotyping was associated with substantially increasing risk of allopurinol-induced SCARs (odds ratio 117.6; 95% CI 70.3 to 196.8; I2 = 45%) regardless of the subgroups. We found a higher prevalence of HLA-B*58:01 genotyping in some Asian populations compared with the Whites. There is evidence to confirm a strong association between this allele and allopurinol-induced SCARs.